Adsorption behaviour of SO2 molecules on unburned carbon from lignite fly ash in the context of developing commercially applicable environmental carbon adsorbent. (1st July 2022) - Kisiela-Czajka, Anna M.
Abstract: In order to study the nature of SO2 binding, the effect of the presence of H2 O(g) and O2 in the gas mixture was investigated, the pore size distribution (using nitrogen at 77 K) and the porosity of the bed were determined, qualitative and quantitative analysis of the oxygen surface functional groups (using thermal and infrared spectroscopy, acid-base titration, electrochemical analyses) and ash minerals (ICP-OES) were carried out. It was proved that the adsorbed SO2 can form surface complexes with aluminum oxide (aluminum sulfate) and/or with a phenolic group (sulfone group). In the presence of the SO2 +Ar, the permanent oxidation of SO2 to SO3 was not confirmed. The addition of H2 O(g) does not improve the SO2 binding efficiency, unlike the addition of O2 . The physical binding of SO2 is at a higher level for carbon beds characterized by higher bed porosity, and the increase in chemically adsorbed SO2 occurs due to an increase in acidity and a decrease in the total alkalinity of unburned carbons. Regardless of the gas mixture composition, a positive effect of C–OH and CO groups on SO2 binding was recorded. Graphical abstract: Image 1 Highlights: Polydisperse porous structure and predominance of thermally stable functional groups. Positive effect of C–OH and CO groups on the efficiency of SO2 bonding. C–OH group may bond with SO2 forming sulfone group (-SO3 H). Exposure of Al2 O3 in ash to SO2 may form surface aluminum sulfates. No permanent adsorption of SO2 to SO3 in an atmosphere free of O2 and H2 O(g) .